Implementation of Organizational Structure in Gantar District, Indramayu Regency - Ismanudin; Ayu Rochani Sujadi (Public Policy: Jurnal Ilmu Sosial dan Kebijakan, 2024)
This research aims to discuss the implementation of the sub-district organizational structure after the expansion of sub-districts in Gantar District, Indramayu Regency in 2003.  The results of this research show that the implementation of the sub-district organizational structure in Gantar District is not yet completely optimal.  This can be seen from (a) type of organization, (b) organizational department, (c) position and type of authority of officials, (d) field and employment relationship, (e) line of orders and responsibilities, (f) range of control and organizational leadership system which in general still shows that it has not been implemented effectively.